NATIONAL IDENTITY OF A MEMBER STATE IN EUROPEAN UNION LAW IN THE CONTEXT OF RELOCATION OF MIGRANTS - Stępkowski, Łukasz (Review of European and Comparative Law, 2020)
This paper addresses the issue of national identity, a legal concept found under Article 4(2) of the Treaty on European Union, while assessing the so-called ‘relocation’ regime, introduced by the European Union to address the recent migratory pressure on Italy and Greece. Descriptive approach is used in regard to methodology and attention is given to the case law of the CJEU.